Pengaruh Model Pembelajaran Reciprocal Learning Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran IPS Terpadu Kelas VIII di SMP Negeri Widyakrama Kabupaten Gorontalo - Sudirman; Ervina Pombaile (Yayasan Pendidikan Sudirman Mandiri, 2024)
The purpose of the study was to determine the influence of reciprocal learning model on student’s learning motivation in integrated social science subject in class VIII of SMP Widyakrama State Junior High School of Gorontalo Regency. This is a quantitative research that used ex post facto method, involving th entire students of class VIII as the population as weel as the sample using total sampling technique. While the data analysis used hyotesis testing technique of simple linear regression analysis. The findings showed that the hypothesis had positive and significant effect on students’ lerning motivation. The positive coefficient indicated thaht the better the model the higher the motivation would be, obtaining 0,638 value of determinant (63,80%). While the rest (37,20%) was influenced by other factors not examined such as teachers’ exemplariness and teaching skill, student’ ability, students’ willingness in learning and students talents